International harm reduction indicators are still not reached: results from a repeated cross-sectional study on drug paraphernalia distribution in Germany, 2021 - Franziska Hommes; Amrei Krings; Achim Dörre; Esther Neumeier; Dirk Schäffer; Ruth Zimmermann (BMC, 2023)
Abstract Background To prevent the transmission of blood-borne infections and reach the elimination of viral hepatitis by 2030, the World Health Organization (WHO) has set the goal to distribute 300 sterile needles and syringes each year per person who injects drugs (PWID). We aimed to assess drug paraphernalia distribution in Germany in 2021, including the WHO indicator, and to analyse changes to the distribution measured in 2018. Methods We conducted a repeated cross-sectional study of low-threshold drug services in Germany. We assessed type and quantity of distributed drug paraphernalia and the number of supplied PWID in 2021 using an online and paper-based questionnaire. We conducted a descriptive statistical analysis of data from 2021, assessed fulfillment of the WHO indicator and changes in services that participated 2021 and in the previous study 2018. Results Five hundred and eighty-nine of 1760 distributed questionnaires were returned in 2021. 204 drug services from 15 out of 16 federal states confirmed drug paraphernalia distribution, covering 20% of Germany's rural and 51% of urban counties. 108 services had also participated in 2018. The most frequently distributed paraphernalia for injecting drug use in 2021 were syringes (97% of services), needles (96%) and vitamin C (90%). Pre-cut aluminium foil (79% of services) and pipes (28%) for inhaling, and sniff tubes (43%) for nasal use were distributed less frequently. We found a median reduction in distributed syringes by 18% and by 12% for needles compared to 2018. Of 15 states, two reached the 2030 WHO-target for needles and one for syringes. Conclusions The current national estimates and changes from 2018 to 2021 for drug paraphernalia distribution seem far from meeting the WHO target. Reasons could include a change in drug consumption behaviour towards less injecting use and more inhaling, and effects of the COVID-19 pandemic (supply difficulties, social distancing, lockdown, reduced opening hours of services). We observed pronounced regional differences in drug paraphernalia distribution. To close existing gaps, Germany should expand its drug paraphernalia distribution programmes and other harm reduction services, such as drug consumption rooms. Further investigation of determinants for adequate distribution is essential to reduce blood-borne infections in this key population.